Aging and Autophagy in the Heart. Issue 10 (13th May 2016) - Shirakabe, Akihiro; Ikeda, Yoshiyuki; Sciarretta, Sebastiano; Zablocki, Daniela K.; Sadoshima, Junichi
Abstract : The aging population is increasing in developed countries. Because the incidence of cardiac disease increases dramatically with age, it is important to understand the molecular mechanisms through which the heart becomes either more or less susceptible to stress. Cardiac aging is characterized by the presence of hypertrophy, fibrosis, and accumulation of misfolded proteins and dysfunctional mitochondria. Macroautophagy (hereafter referred to as autophagy) is a lysosome-dependent bulk degradation mechanism that is essential for intracellular protein and organelle quality control. Autophagy and autophagic flux are generally decreased in aging hearts, and murine autophagy loss-of-function models develop exacerbated cardiac dysfunction that is accompanied by the accumulation of misfolded proteins and dysfunctional organelles. On the contrary, stimulation of autophagy generally improves cardiac function in mouse models of protein aggregation by removing accumulated misfolded proteins, dysfunctional mitochondria, and damaged DNA, thereby improving the overall cellular environment and alleviating aging-associated pathology in the heart. Increasing lines of evidence suggest that autophagy is required for many mechanisms that mediate lifespan extension, such as caloric restriction, in various organisms. These results raise the exciting possibility that autophagy may play an important role in combating the adverse effects of aging in the heart. In this review, we discuss the role of autophagy in the heart during aging, how autophagy alleviates age-dependent changes in the heart, and how the level of autophagy in the aging heart can be restored.